CFD investigation of inlet pressure effects on the energy separation in a vortex tube with convergent nozzles. Issue 5 (6th July 2015) - Pourmahmoud, Nader; Rashidzadeh, Masoud; Hassanzadeh, Amir
Abstract : Purpose: – The purpose of this paper is to investigate the effect of convergent nozzles on the thermal separation inside a vortex tube, using a three-dimensional (3D) computational fluid dynamics (CFD) model as predicting tool. Design/methodology/approach: – The 3D finite volume formulation with the standard k-ε turbulence model has been used to carry out all the computations. Six different nozzles for convergence angle have been utilized β=0, 2, 4, 6, 8 and 10°. All other geometrical parameters were considered fixed at the experimental condition, i.e. main tube and chamber sizes and 294.2 K of gas temperature at inlets. Findings: – The numerical results present that there is an optimum convergence angle for obtaining the highest efficiency and β=2° is the optimal candidate under the simulations. It can be pointed that, some numerical data are validated by the available experimental results which show good agreement. Practical implications: – It is a useful and simple design of nozzle injectors to achieve the maximum cooling capacity. Originality/value: – In the work with assuming the advantages of using convergent nozzles on the energy separation and their considerable role on the creation of maximum cooling capacity of machine, the shape of nozzles was concentrated. This research believes that choosing an appropriate convergence angle is one of the important physical parameters. So far, an effective investigation toward the optimization of convergent nozzles has not been done but the importance of this subject can be regarded as an interesting research theme; so that the machine would operate in the way that the maximum cooling effect or the maximum refrigeration capacity is provided.